Gesture controlled human-computer interface for the disabled - Oskar M. Szczepaniak; Dariusz J. Sawicki (Nofer Institute of Occupational Medicine, 2017)
Background: The possibility of using a computer by a disabled person is one of the difficult problems of the human-computer interaction (HCI), while the professional activity (employment) is one of the most important factors affecting the quality of life, especially for disabled people. The aim of the project has been to propose a new HCI system that would allow for resuming employment for people who have lost the possibility of a standard computer operation. Material and Methods: The basic requirement was to replace all functions of a standard mouse without the need of performing precise hand movements and using fingers. The Microsoft's Kinect motion controller had been selected as a device which would recognize hand movements. Several tests were made in order to create optimal working environment with the new device. The new communication system consisted of the Kinect device and the proper software had been built. Results: The proposed system was tested by means of the standard subjective evaluations and objective metrics according to the standard ISO 9241-411:2012. The overall rating of the new HCI system shows the acceptance of the solution. The objective tests show that although the new system is a bit slower, it may effectively replace the computer mouse. Conclusions: The new HCI system fulfilled its task for a specific disabled person. This resulted in the ability to return to work. Additionally, the project confirmed the possibility of effective but nonstandard use of the Kinect device. Med Pr 2017;68(1):11-21